Adsorption behaviour of cefapirin on mild steel in hydrochloric acid solution - Singh A.K.; Ebenso E.E.; Quraishi M.A. (My University, 2025)
The adsorption behaviour of cefapirin (CFP) on mild steel (MS) in 1 M HCl solution was studied using potentiodynamic polarization, electrochemical impedance spectroscopy (EIS) and weight loss techniques. The surface morphology of the MS after its exposure to 1 M HCl solution with and without 400 ppm CFP was examined using scanning electron microscopy (SEM). The value of activation energy (E a), Arrhenius factor, enthalpy and entropy for the MS corrosion inhibition and the thermodynamic parameters such as adsorption equilibrium constant (K ads), free energy of adsorption (ΔG 0 ads), adsorption heat (ΔH 0 ads) and adsorption entropy (ΔS 0 ads) values were calculated and discussed. The adsorption behaviour of CFP is experimentally investigated by contact angle measurement on mild steel surface. The hydrophobic character of MS increased with increasing concentration of CFP. The results showed that CFP performed excellent inhibiting effect for the corrosion of the MS. © 2012 by ESG.